An Empirical Investigation on Spot and Futures Market With Reference to Energy Sector on NSE - Ram, Dr. P. Sri (International Journal of Scientific Research and Management (IJSRM), 2017)
The importance of volatility is widespread in the area of financial economics. Equilibrium prices, obtained from asset pricing models, are affected by changes in volatility, investment management lies upon the mean-variance theory, while derivatives valuation hinges upon reliable volatility forecasts. Portfolio managers, risk arbitrageurs, and corporate treasurers closely watch volatility trends, as changes in prices could have a major impact on their investment and risk management decisions. Volatility may be defined as the degree to which asset prices tend to fluctuate. Volatility is the variability or randomness of asset prices. Volatility is often described as the rate and magnitude of changes in prices and in finance often referred to as risk. This study has been carried out on Spot and Futures market with reference to energy sector stocks on NSE. It also analysed the co-integration and Causal relationship between Spot and Futures prices of stocks and index. The study also estimated the impact of Spot market on Futures market. The study has been carried out on volatility of Indian Stock Market represented by S&P CNX Nifty Index along with influence by energy sector stocks.